Efektivitas Program Bantuan Stimulan Perumahan Swadaya (BSPS) dalam Penyediaan Rumah Layak Huni di Kelurahan Belawan Bahari, Medan Belawan, Kota Medan - Taty Kristina Malau; Agus Suriadi; Mia Aulina Lubis (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Low-Income Communities (MBR) often live in Uninhabitable Houses (RTLH) due to financial constraints, which hinder their ability to improve their welfare and meet their basic living needs. The government is responsible for fulfilling the need for Decent Housing (RLH) for the community, which is realized through the Stimulant Assistance for Self-Help Housing (BSPS) program. The BSPS program aims to improve the quality of housing for the community through financial assistance and empowerment. This research was conducted in Belawan Bahari Village, Medan Belawan District, Medan City, which is a coastal area prone to tidal flooding. The main informants in this study were the Chairpersons of Assistance Recipient Groups I and II of the BSPS Program. Additional informants included the Head of Neighborhood Unit XII in Belawan Bahari Village. Key informants consisted of the Commitment Making Officer for Self-Help Housing and RUK, as well as Technical Experts from BSPS who are responsible for the activities and implementation of the BSPS program in Belawan Bahari. Data collection techniques were carried out through literature studies and field studies, including observation, interviews, and documentation. The data obtained in the field were then analyzed qualitatively by the researcher to draw conclusions from the research findings. The results indicated that the BSPS program in Belawan Bahari Village was effective in providing decent housing for aid recipients. This effectiveness was assessed based on program effectiveness indicators determined by Sutrisno, demonstrating success in terms of program understanding, targeting accuracy, timeliness of implementation, achievement of objectives, and tangible changes for aid recipients. Decent housing was evaluated based on building durability, adequacy of living space, access to safe drinking water, proper sanitation, as well as lighting and ventilation.